Perbedaan Faktor Yang Menjadi Pertimbangan Mahasiswa Memilih Perguruan Tinggi Di Surabaya - Bruno Hami Pahar (BIP's JURNAL BISNIS PERSPEKTIF, 2020)
This study aims to determine the differences in factors that students consider when choosing tertiary institutions in Surabaya. The population in this study were first semester students in 5 tertiary institutions namely Surabaya Institute of Technology (ITS), Widya Mandala Catholic University of Surabaya (UKWM), Surabaya University (UBAYA), Darma Cendika Catholic University (UKDC), and Petra Christian University (UKP), with a total sample of 100 students. This research was analyzed using different tests and to test the differences between three or more independent groups of two or more variables, using the Kruskal Wallis statistical method. The results showed that there were differences in factors that were considered by students to choose tertiary institutions in Surabaya, with nine factors examined, there were eight different variables among the five tertiary institutions studied, namely location (X1), reputation (X2), scholarship (X3), tuition fees (X4), entry requirements (X5), facilities (X6), number of students (X7), lecturer competencies (X8), and campus buildings (X9). The test results stated the scholarship factor (X3) there was no difference between the five tertiary institutions studied, because the H count was 7.78 < H table (9,488) and asymp. sig 0,100 > 0.05. There are differences from 8 existing factors, namely: 1) There are differences in the consideration factors of prospective students between Darma Cendika Catholic University (UKDC) with Surabaya Institute of Technology (ITS), Widya Mandala Catholic University of Surabaya (UKWM), Surabaya University (UBAYA), and Petra Christian University (UKP), namely reputation, tuition fees, entry requirements, facilities, number of students, competencies lecturers, and campus buildings, because the calculated H value > H table (3,841) and asymp. sig < 0.05,